2023
DOI: 10.1055/a-2039-3017
|View full text |Cite
|
Sign up to set email alerts
|

„Hilflosigkeit, das Abgeben jeglicher Selbstverantwortung und Selbstbestimmtheit“ – eine qualitative Auswertung von traumatisierenden Geburtserlebnissen in Relation zum Geburtsmodus

Abstract: ZusammenfassungHintergrund Eine Geburt verbindet emotionale Herausforderungen mit individuellen Ängsten. Unerwartete Geburtsverläufe können Stressreaktionen bis hin zu posttraumatischen Belastungsstörungen auslösen.Ziel der Studie Das Ziel der Studie war die qualitative Beschreibung von belastend wahrgenommenen Geburtserlebnissen und gewünschten Maßnahmen nach traumatisierenden Geburtserlebni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…These results are similar to the ndings in another study mentioned here in the introduction [12]. The study observed similar categories as in the present report.…”
Section: Discussion and Prognosissupporting
confidence: 94%
See 2 more Smart Citations
“…These results are similar to the ndings in another study mentioned here in the introduction [12]. The study observed similar categories as in the present report.…”
Section: Discussion and Prognosissupporting
confidence: 94%
“…The sense of a lack of control along with a lack of selfe cacy were identi ed also in further studies as signi cant components of adverse or traumatizing birthing experiences [10,11]. To our knowledge, with regards to the German health care system only one study exists that analyzes reports of birthing experiences to establish a connection to the delivery mode [12]. The researchers came to the conclusion that an unplanned course of events during childbirth was more closely related to a higher risk of mental stress as well as feeling of guilt.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation